Construct validation of the Narcissistic Admiration and Rivalry Questionnaire in Spanish-speaking countries: Assessment of the reliability, structural and external validity and cross-cultural equivalence (2019)
A recent re-operationalisation of grandiose narcissism has resulted in the distinction of two narcissistic strategies based on the cognitive, affective-motivational and behavioural dynamics: admiration (assertive self-enhancement) and rivalry (antagonistic self-protection). The Narcissistic Admiration and Rivalry Questionnaire (NARQ) was developed to assess this model with two higher-order dimensions. However, cross-validations of the NARQ have not been extensively conducted across diverse population groups and languages. This study aimed to test the internal and external validity (through the relation with envy and self-esteem), reliability and cross-cultural equivalence of the Spanish version of the NARQ. The psychometric properties were evaluated in a Spanish sample (N = 310), and cross-cultural equivalence was tested in participants from Chile (N = 234) and Colombia (N = 256). The results supported the reliability and validity of the Spanish NARQ, as well as the cross-cultural equivalence across Spanish-speaking countries. In addition, we discuss obtained differences across Spanish, Chilean and Colombian sample within two narcissistic strategies. © 2019 International Union of Psychological Science